Aspectos fisiológicos e bioquímicos do tambaqui (Colossoma macropomum, Cuvier 1818) alimentado com dietas suplementadas por frutos e sementes de áreas alagáveis - Oliveira, Alzira Miranda de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2005)
The high productivity of the floodplain areas of the Amazon in conjunction to the need of alternative food for confined fish, raise great interest in verifying the possibility of the use of regional fruits to reduce the costs of tropical fish farming. This study aimed to evaluate the potentiality of catoré (Crataeva benthami), camu-camu (Myrciaria dubia), embaúba (Cecropia latiloba) and jauari (Astrocaryum jauari) fruits and munguba (Pseudobombax munuba) seed in the tambaqui (Colossoma macropomum) feeding, through the analysis of physiological and biochemical aspects of this fish species. The results showed that the fruits and the seed did not cause organic disequilibrium or growth impairment of the animals. However, it was observed that the diet supplemented with camu-camu and jauari presented larger similarity to the control group, emerging as alternatives among the tested diets.
Keywords: Tambaqui; Frutos e sementes; Alimentação do Tambaqui